Clinical effect of closed reduction minimally invasive fixation in intra-articular comminuted fractures of the femoral condyle - Lian, Xiaodong; Zhang, Heng; Guo, Fan; Wang, Zhongzheng; Zhao, Kuo; Hou, Zhiyong; Zhang, Yingze (Frontiers in Surgery, 2023)
Objective To evaluate the advantages of double reverse traction closed reduction combined with minimally invasive fixation in treating femoral condylar comminuted fractures. Methods We retrospectively enrolled a total of 24 patients with femoral condylar comminuted fractures (AO = 33C3) admitted to Third Hospital of Hebei Medical University from March 2018 to February 2020. The patients were divided into two groups: experimental group (double reverse traction, n = 12) and control group (conventional surgery, n = 12). Patient demographics, fracture characteristics, operation time, incision length, and postoperative complications were then collected. The Hospital for Special Surgery (HSS) scores were recorded at the last follow-up visit. Results The average surgical time was 52.2 (41–73) min in the experimental group and 71.2 (45–103) min in the control group. In addition, the mean total incision length was 13.8 (11–17) cm in the experimental group and 16.3 (14–19) cm in the control group. The average HHS scores at the final follow-up were 86.3 (78–93) and 82.7 (76–90) in the experimental group and control group, respectively. Conclusion It was found that double reverse traction closed reduction combined with minimally invasive fixation can provide good repositioning results and functional extremity. Moreover, patients tolerate postoperative functional knee exercises well.